The Role of Performance Appraisal on Educator Retention and Motivation in Islamic Junior School - Setiawan, Andi; Huzali, Ikhsan; Wafiroh, Nihayatul (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Educator performance appraisal in Islamic Junior School has a significant role in improving educator motivation and retention. This study aims to explore the relationship between performance appraisal and educators' motivation and decision to remain teaching in the institution. Through a qualitative approach, this study involved in-depth interviews with educators at Islamic Junior School. The data obtained was analyzed using thematic analysis method to identify emerging patterns and themes. The results showed that performance appraisals conducted in a transparent and fair manner can increase educators' motivation, as they feel valued and recognized for their contributions. In addition, constructive feedback from performance appraisals serves as a professional development tool that encourages educators to improve their teaching quality. The study also found that the presence of a good appraisal system contributes to educator retention rates, where educators who feel supported and valued tend to stay longer in the institution. Thus, this study recommends the development of a more inclusive and participatory performance appraisal system, as well as training for educators to understand and utilize the appraisal results in their professional development. The findings are expected to contribute to human resource management in Islamic Junior School and improve the overall quality of education.